Opening The Door: Immigration and Integration of Holocaust Survivors in Vancouver, 1947-1970 - Gerber, Jean (Canadian Jewish Studies / Études juives canadiennes, 1997)
Holocaust survivors who came to Canada have been characterizedas alienated from Canadian Jewish life. Often, however, noobjective study has been conducted of how survivors interactedwith the economic, social and cultural life of their host communitiesin order to substantiate this claim. This paper studiessurvivors’ residential and occupational patterns after coming toVancouver, and examines their affiliations with communityorganizations. It combines objective data with oral interviewsto demonstrate how survivors integrated into the Vancouverhost Jewish community and whether or not they remainedalienated from it.